Large Magnetoconductance in GaAs Induced by Impact Ionization - Kim, Taeyueb; Joo, Sungjung; Koo, Hyun Cheol; Hong, Jinki (KOREAN PHYSICAL SOC, 2019)
We have investigated this magneto-switching behavior in GaAs structure. Exposing these devices to a small magnetic field (< 0.5 Tesla) induced a change in conductance that was above 100,000% at 10 K and up to 1,000% at 300 K. We also observed a variety of transport mechanisms in a single device that were clearly distinguished according to the bias voltage and their characteristic magnetoconductance can be specified. This work represents important progress in understanding the physics of the magneto-switching function and achieving large ON/OFF ratios.
Keywords: CHARGE-LIMITED CURRENTS